Longer observation time increases adenoma detection in the proximal colon – a prospective study - Peter Klare; Henrik Phlipsen; Bernhard Haller; Henrik Einwächter; Andreas Weber; Mohamed Abdelhafez; Monther Bajbouj; Hayley Brown; Roland M. Schmid; Stefan von Delius (Endoscopy International Open, 2017)
Background and study aims Longer observation times are associated with increased adenoma detection rates (ADR) in the entire colon. However, adenomas in the proximal colon are at risk of being missed during colonoscopy. The aim of this study was to investigate the impact of observation time on detection of adenomatous polyps in the proximal colon. Patients and methods This was a prospective study at a university hospital in Germany. Colonoscopies were conducted using magnetic endoscope imaging (MEI) in order to determine the exact position of the scope. Exact observation times spent for the detection of polyps in the proximal and distal colon segments were assessed. The primary outcome was adenoma detection in the proximal colon. ROC curves were generated in order to test the correlation between observation time and adenoma detection. Logistic regression analysis was used to check for interfering factors. Results A total 480 procedures with 538 polyps were available for analysis. The overall adenoma detection rate was 38.5 %. ADR in the proximal colon was 28.0 %. There was a significant association between observation time in the proximal colon and the detection of proximal adenomas (P < 0.001). The impact of the time factor on ADR was stronger in the proximal compared to the distal colon (P = 0.030). A net period of 4 min 7 sec was found to be the minimum time span for sufficient adenoma detection in the proximal colon. Conclusion Observation time is significant in terms of adenoma detection in the proximal colon. The impact of observation time on ADR is stronger in the proximal compared to the distal colon. In the proximal colon a minimum time span of 4 minutes should be spent in order to ensure adequate adenoma detection. ClinicalTrials.gov identifier: NCT02819492